Facilitating newcomer motivation through internalization: A self-determination theory perspective on newcomer socialization - Chong, Jane; Gagné, M.; Dunlop, Patrick; Wee, S. (2024)
Despite the importance of employee work motivation in organizations, little is known about how newcomers develop high-quality motivation to function optimally at work. We propose internalization — a process whereby newcomers take in external information and values learned during the socialization period to become their own — as a key process that is critical for developing said motivation. Drawing on self-determination theory, this article introduces a model of socialization that proposes the need satisfaction of competence, relatedness, and autonomy as important proximal outcomes for internalization and successful socialization. We discuss theoretical and practical implications for facilitating a motivated and proactive workforce critical for today's dynamic organizational landscape.